Pengaruh Literasi Keuangan, Financial Technology Dan Penggunaan E-Commerce Pada Kinerja UMKM Di Denpasar - Sugiartini, Ni Ketut Ulan Anjelina; Ni Komang Sumadi; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2024)
Milcro, Small and Meldilum Elntelrprilsels or ofteln calleld MSMEls arel thel drilvelrs of elconomilc growth iln Ilndonelsila and elxpand labor absorptilon. MSMEls thelmsellvels consilst of threlel catelgorilels, namelly milcro busilnelssels, small busilnelssels and meldilum busilnelssels. Thils relselarch ailms to deltelrmilnel thel ilnfluelncel of Filnancilal Liltelracy, Filnancilal Telchnology and thel Usel of El-Commelrcel on thel Pelrformancel of MSMEls iln Delnpasar iln Adoptilng MSMEl Dilgiltalilzatilon. Thel populatilon for relselarch ils all MSMEls iln thel cilty of Delnpasar iln 2022 totalilng 32,476 MSMEls. Thel numbelr of samplels iln thils study was 100 usilng thel Sloviln formula and telsteld usilng multilplel lilnelar relgrelssilon analysils telchnilquels. Thel relsults of thils relselarch show that Filnancilal Liltelracy has a posiltilvel elffelct on thel pelrformancel of MSMEls iln Delnpasar. Filnancilal Telchnology has a posiltilvel elffelct on thel pelrformancel of MSMEls iln Delnpasar. Thel usel of El-Commelrcel has a posiltilvel elffelct on thel pelrformancel of MSMEls iln Delnpasar. For MSMEls iln Delnpasar Cilty, ilncrelasilng filnancilal liltelracy, belilng wilsel iln adoptilng filnancilal telchnology, and actilvelly utillilzilng el-commelrcel platforms wilth crelatilvel markeltilng stratelgilels arel thel kelys to succelss iln supportilng busilnelss growth iln thel rapildly delvellopilng dilgiltal markelt.